2017
DOI: 10.1002/lary.26661
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive vestibular rehabilitation technique

Abstract: 2b. Laryngoscope, 128:713-718, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
12
0
2
Order By: Relevance
“…Both intervention groups improved significantly compared with usual care for dizziness handicap and vertigo symptoms and there were no differences between the intervention groups. At-home DVA training using software algorithms to determine optotype size and wearable sensors to track head velocity led to reduction in DHI scores in a small sample of individuals with UVH (Crane and Schubert,167 level III). Software algorithms have the potential to remotely supervise exercise participation based on predefined objective criteria such as symptom reports, DVA score, or peak head velocity.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both intervention groups improved significantly compared with usual care for dizziness handicap and vertigo symptoms and there were no differences between the intervention groups. At-home DVA training using software algorithms to determine optotype size and wearable sensors to track head velocity led to reduction in DHI scores in a small sample of individuals with UVH (Crane and Schubert,167 level III). Software algorithms have the potential to remotely supervise exercise participation based on predefined objective criteria such as symptom reports, DVA score, or peak head velocity.…”
Section: Update and Revision Of Guidelinesmentioning
confidence: 99%
“…Crane and Schubert 167 (level III) studied individuals with chronic UVH with DHI scores of greater than 30 out of 100. In this small study (n = 4), subjects performed a 10-minute daily computer-based DVA task that encouraged angular head velocity.…”
Section: Evidence Updatementioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Sparrer et al [ 27 ] who divided their patients into the experimental group who performed customized exercise using the Nintendo Wii Balance Board with medication treatment, and a control group who performed exercise with medical treatment for patients with vestibular neuritis, a significant decrease in dizziness was observed in the experimental group, and the patients’ return to everyday life was faster in the experimental group than in the control group. Crane and Schubert [ 28 ] showed an average decrease of 71% in dizziness after one month of implementing a computer-based adaptation of the vestibular rehabilitation program as compared to the traditional VRE. Preceding studies suggest that habituation exercises can reduce symptoms even if the same situation occurs by repeatedly performing various postures or situations in everyday life in which the patient's symptoms occur.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due in part to a lack of equipment in the clinical and home setting to measure speed and/or excursion of head movement. However, our review found several different technologies being used or in development that can assist with measuring speed and excursion 17 19–22 26 31–33. Most involved wearable head mounted technology that might be more accessible to a clinical environment 19 20 22 31–33.…”
Section: Discussionmentioning
confidence: 99%